Acessibilidade de leitura para cegos com o projeto Celta numa Raspberry PI - Santos, Juan Henrique dos (2023)
Braile reading is fundamental to include visually impaired people in the access to information, it‘s a type of literacy and communication able to include everyone in society allowing then access to knowledge and culture. This tactile reading can be found in diffrents formats such as embossed paper or even in a much more complex way, like a braile display. The Celta project, elaborated by SEaD-UFSCar squad funded by CAPES, had as objective the development of a low cost hardware and software to braile reading. By the end of project were elaborated intructions manuals for replications and advertising material, there was a contextualization and clarification about the use and applicability of Celta. The present work aims to continue the development of the Celta project by promoting a technological update of this equipment. This update involves replacing the Arduino microcontroller with the Raspberry Pi computer. Through this replacement, it becomes possible to implement new advancements, such as replacing serial communication with wireless communication using sockets. In the Raspberry Pi, port programming is carried out using the Python language, while in the desktop application, a software developed in Java is used to extract text from .PDF and .TXT files. The use of Python and Java languages makes the project more user-friendly and accessible to developers, taking advantage of the popularity of these communities. These changes result in greater convenience for equipment users.